Effectiveness of subcutaneous low-dose alemtuzumab and rituximab combination therapy for steroid-resistant chronic graft-versus-host disease - Gutiérrez Aguirre, César Homero; Cantú Rodríguez, Olga Graciela; Borjas Almaguer, Omar David; González Llano, Óscar; Jaime Pérez, José Carlos; Solano Genesta, M.; Gómez Guijosa, Miguel Ángel; Mancías Guerra, María del Consuelo; Tarín Arzaga, Luz del Carmen; Gómez Almaguer, David (2012)
Background Chronic graft-versus-host disease is a common late complication of allogeneic hematopoietic stem cell transplantation. Corticosteroids are the standard initial treatment. Second-line treatment has not been well defined. We evaluated the effectiveness and safety of low doses of alemtuzumab plus low doses of rituximab in the treatment of steroid-refractory chronic graftversus-host disease. Design and Methods Ten men and 5 women were prospectively included in the study. All patients received one cycle of subcutaneous alemtuzumab 10 mg/day/3 days and intravenous rituximab 100 mg on Days +4, +11, +18 and +25. The therapeutic response was measured on Days +30, +90 and +365 of the protocol. Results Median age was 41 years. The main site involved was the oral mucosa (86.7%) followed by the eyes (66.7%), liver (60%), skin (53%), lungs (13.3%) and intestinal tract (6.7%). The overall response was 100% at Day +30 evaluation: 10 patients (67%) had partial remission, 5 (33%) had complete remission. At Day +90 evaluation, 7 (50%) patients had partial remission, 4 (28%) had complete remission; 3 (21%) had relapsed chronic graft-versus-host disease and one patient did not reach the evaluation time point. So far, 5 patients have reached the Day +365 follow-up evaluation; 2 (40%) had partial remission, 2 had complete remission and one experienced chronic graft-versus-host disease progression. Adverse effects were mainly infections in 67% of patients; these were all quickly solved, except for one patient who died from pneumonia. Conclusions This combination therapy appears to be an efficacious and safe treatment for steroid-refractory chronic graft-versus-host disease. Longer follow up to determine the durability of response and survival is required (ClinicalTrials.gov: NCT01042509).